Nine months after the tsunami: Hopes for peace in Aceh - Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2005)
The breakthrough in the Helsinki negotiations between the Indonesian government and the Free Aceh Movement (Gerakan Aceh Merdeka, GAM) came on August 15, 2005. Months of talks had brought about an end a civil war that had dragged on for more than thirty years in the resource-rich province at the northern tip of the Indonesian island of Sumatra. The aftermath of the Indian Ocean tsunami of 26 December 2004 was a crucial factor in bringing the parties back to the negotiating table and producing a constructive outcome. (SWP Comments / SWP)
Keywords: 320